2017
DOI: 10.1093/nar/gkx209
|View full text |Cite
|
Sign up to set email alerts
|

Uracil DNA glycosylase (UDG) activities in Bradyrhizobium diazoefficiens: characterization of a new class of UDG with broad substrate specificity

Abstract: Repair of uracils in DNA is initiated by uracil DNA glycosylases (UDGs). Family 1 UDGs (Ung) are the most efficient and ubiquitous proteins having an exquisite specificity for uracils in DNA. Ung are characterized by motifs A (GQDPY) and B (HPSPLS) sequences. We report a novel dimeric UDG, Blr0248 (BdiUng) from Bradyrhizobium diazoefficiens. Although BdiUng contains the motif A (GQDPA), it has low sequence identity to known UDGs. BdiUng prefers single stranded DNA and excises uracil, 5-hydroxymethyl-uracil or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The small ssDNA sections that become available when individual DNA binding domains of RPA locally dissociate may be accessed by other proteins such as UNG2 [55] . Consistent with this idea, the catalytic domain of UNG2 binds small ssDNA sections that are similar in size to sites occupied by individual DNA binding domains of RPA (4–6 nt) and with similar association rates [48,49,55,59,60] . We speculate that the relatively high turnover by the covalent complex on 31 nt ssDNA indicated that RPA−Spy−UNG2 could participate in a handoff of ssDNA from the RPA portion of the complex to its UNG2 portion.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The small ssDNA sections that become available when individual DNA binding domains of RPA locally dissociate may be accessed by other proteins such as UNG2 [55] . Consistent with this idea, the catalytic domain of UNG2 binds small ssDNA sections that are similar in size to sites occupied by individual DNA binding domains of RPA (4–6 nt) and with similar association rates [48,49,55,59,60] . We speculate that the relatively high turnover by the covalent complex on 31 nt ssDNA indicated that RPA−Spy−UNG2 could participate in a handoff of ssDNA from the RPA portion of the complex to its UNG2 portion.…”
Section: Resultsmentioning
confidence: 64%
“…[55] Consistent with this idea, the catalytic domain of UNG2 binds small ssDNA sections that are similar in size to sites occupied by individual DNA binding domains of RPA (4-6 nt) and with similar association rates. [48,49,55,59,60] We speculate that the relatively high turnover by the covalent complex on 31 nt ssDNA indicated that RPAÀ SpyÀ UNG2 could participate in a handoff of ssDNA from the RPA portion of the complex to its UNG2 portion. This would imply that the two proteins do not need to physically dissociate for the handoff to occur, and that the winged-helix domain of RPA2 is not strictly required for the handoff other than to serve as a means for RPA to spatially recruit UNG2 to the ssDNA substrate.…”
Section: Activity Of Rpa Ung2 and The Rpaà Spyà Ung2 Complex On Ssdnamentioning
confidence: 96%
“…The concentrations of Nsa UNG versus Ugi are shown in molar ratio. (B) Gel mobility shift analysis of binding between Ugi and hUNG /Nsa UNG . After incubation of enzyme with/without Ugi, reaction products were separated on 15% native PAGE gel in Tris‐glycine buffer ( pH 8.5).…”
Section: Resultsmentioning
confidence: 99%
“…The arr gene was PCR amplified from M. smegmatis genomic DNA using the primers arr_NdeI_fp and arr_HindIII_rp and Pfu DNA polymerase. The amplicon of 440 bp obtained was gel purified and ligated to pTrcNdeIHis vector (41) to generate pTrcNdeIHis-arr. Further, pTrcNdeIHis-arr was digested with NcoI and HindIII to release arr fragment and subcloned into pACDH plasmid at the same restriction site to generate The PCR conditions were the following: initial denaturation at 94°C for 5 min and 94°C for 1 min, annealing at a gradient of 52°C to 60°C, extension at 70°C for 11 min, and a final extension at 70°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%